FLEXIBLE SPECIALISATION AND UK MANUFACTURING WEAKNESS: A COMMENT ON HIRST AND ZEITLIN. - Nolan, Peter; O'Donnell, Kathy (Political Quarterly)
In a recent analysis of British manufacturing performance, P. Hirst and J. Zeitlin challenge the idea that the Thatcher government's programme of selective supply side measures has succeeded in reversing industry's fortunes. Hirst and Zeitlin's policy proposals are rooted in a conceptual framework which oversimplifies the development of industrial organisation in Britain and misrepresents the record of state industrial policy in the post-war years. To be sure, public ownership has been an important feature of the post war British economy. But, as argued elsewhere, the nationalised industries have tune and again been used by governments to meet short term macroeconomic and political objectives, the consequence of which has been to critically weaken their longterm performance.